Public participation towards environmental issues in Kota Bharu, Kelantan, Malaysia - Rahman, Haliza Abdul (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2011)
Public participation has been recognized as key objectives for local, national and global environmental programmes and has been propagated through the various policies and declarations. Public participation means a process that participate the public in the decision making procedures of an organization. The objective of this paper is to highlight participation of Malaysian public in the environmental issues in order to achieve sustainable development. The study was to identify the public participation in environmental issues in Kota Bharu, Kelantan, Malaysia. The research was based on a set of questionnaire. A total of 200 respondents were interviewed and filled in questionnaire. From the study, Malaysian public are concerned about environment, but their concerns do not naturally translate into action. For Malaysian public participation to be successful, general public should be provided with effective notice of opportunities to participate in environmental issues, and provided with sufficient information to enable them to do so effectively.